2009
DOI: 10.1002/marc.200900243
|View full text |Cite
|
Sign up to set email alerts
|

A Triphenylamine‐Based Conjugated Polymer with Donor‐π‐Acceptor Architecture as Organic Sensitizer for Dye‐Sensitized Solar Cells

Abstract: A conjugated polymer containing an electron donating backbone (triphenylamine) and an electron accepting side chain (cyanoacetic acid) with conjugated thiophene units as the linkers has been synthesized. Dye‐sensitized solar cells (DSSCs) are fabricated utilizing this material as the dye sensitizer, resulting a typical power conversion efficiency of 3.39% under AM 1.5 G illumination, which represents the highest efficiency for polymer dye‐sensitized DSSCs reported so far. The results show the good promise of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
63
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 27 publications
0
63
0
Order By: Relevance
“…To the best of our knowledge, this is one of the most efficient DSSCs employing polymer dye sensitizers. [16] The improved energy conversion efficiency for polymer dye 3-based devices is mainly attributed to the %4.5-fold increase in J sc as compared to that for polymer dye 5-based devices. Considering the fact that 3 and 5 have the same chain length, the obvious difference in J sc indicates that the anchoring group has great effect on the photocurrent generation.…”
Section: à2mentioning
confidence: 98%
See 1 more Smart Citation
“…To the best of our knowledge, this is one of the most efficient DSSCs employing polymer dye sensitizers. [16] The improved energy conversion efficiency for polymer dye 3-based devices is mainly attributed to the %4.5-fold increase in J sc as compared to that for polymer dye 5-based devices. Considering the fact that 3 and 5 have the same chain length, the obvious difference in J sc indicates that the anchoring group has great effect on the photocurrent generation.…”
Section: à2mentioning
confidence: 98%
“…[6,7] Surprisingly polymers, often used in bulk heterojunction plastic solar cells, [8,9] were only sporadically used in DSSC devices as sensitizers. [10][11][12][13][14][15][16] Initially, poor photovoltaic conversion efficiencies with a polythiophene physisorbed on titanium dioxide (TiO 2 ) were reported because of the inefficient penetration of the polymer inside the pores of the TiO 2 film and of the weak electronic communication between the dye and the semiconductor in absence of any anchoring group. [17][18][19] However, short oligothiophene systems functionalized with a binding group such as carboxylic or phosphonic acid efficiently inject electrons in TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The application of conjugated polymers as dye sensitizers in DSSCs has been reported in recent years [16][17][18][19][20]. Studies have shown that triphenylamine-based conjugated polymer with donor-p-acceptor architecture was successfully used as the sensitizer for DSSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, theoretical and experimental studies have demonstrated that the TPA unit, which suppresses the dye aggregation for its nonplanar structure, can be used as the sensitizer of DSSCs [27]. Very recently, a few groups [28][29][30][31][32][33] have reported that DSSCs with various triphenylamine-based dyes have shown PCEs up to ∼7% under AM 1.5 irradiation, indicating the importance of their further investigation in this topic.…”
Section: Introductionmentioning
confidence: 99%